Agricultural Education for Sustainable Growth, Entrepreneurial Skills and Self Reliance - Medhi, Samir (Indian Journal of Hill Farming, 2018)
Post independence, the focus of Government of India was to frame major policies based on equity along with growth in the agriculture sector. Although several efforts have been made towards economic and social stabilization over the past decades but the growth of agro-processing sector which is the focal point of second green revolution for value addition has not been encouraging till date. Farmers still lack access to adequate skill and knowledge in agro-processing sector and its linkage to market is very much poor especially in under developed states. Though the small families has increased their desire level of productivity enhancement but they are unable or ignorant how quality has to be linked with market for better premium due to lack of knowledge and skill. With increase in production, the needs of the day to translate its effect in the process of production is missing. Entrepreneurship is into help a shift which may turn the focus of local government on locally available resources and encourage people to start an enterprise with their idea and creativity. Generally small, and initially financed and operated by a handful of founders or one individual, entrepreneurship are aimed to help bring a shift from agriculture to agribusiness to revitalize Indian agriculture and to make it a more attractive and profitable venture. Among educated agricultural youth, the problem of unemployment can have serious repercussions in terms of social instability which, in turn, may affect governance and growth adversely. Globally, more than 66 per cent of the world’s population is predicted to be urban by 2050. A serious implication of expanding urbanization will be a decline in the rural population. To ensure the sustainability of food production, rural communities, and natural resources, outmigration needs to be reduced by linking agricultural education, which will help to ensure entrepreneurship ability and skill of the local people. Location based crops which are grown and dominant, helps to get not only dividend but also help to recapture the geographical importance, Agricultural Entrepreneurship is a strategic development intervention that has the potential to accelerate the rural development process.